The rise of the Sicilian question in the 1840s: the Italian reaction to geopolitical insecurity in the Mediterranean. Issue 1 (2nd January 2022) - Šedivý, Miroslav
Abstract : During the 1840s Italian society began to see the Mediterranean region as a dangerous place to live, owing to what was regarded as threats represented by Austria, Great Britain, France, and even Russia and the United States. This conviction resulted from various affairs both within and outside Europe, where the same powers were accused of behaving in an overtly aggressive way, which was used as an argument for the political unity of Italy's various states in order to give them greater strength for defence. Since danger was seen all around, this unity became important for both the peninsular Italians and the Sicilians, who agreed on the need to establish an Italian league with federal land and naval forces. The principal objective of this paper is to show that the question of Sicily's future was seen as a question of not only Italy's security, but also of its future position in the Mediterranean as a whole, and that the de facto unanimous support of Sicily's membership in the league in 1848 resulted from this self-protecting response that, moreover, already contained proto-imperialist tendencies in which for geostrategic reasons the island played an important role.